Evolutionary characteristics and community detection of the international metal minerals trade - Zhang, Yanfei; Chen, Qishen; Wang, Kun; Guan, Qing; Xing, Jiayun; Long, Tao; Zheng, Guodong; Li, Mei; Shang, Chenghong; Mao, Jingwen (Frontiers in Physics, 2025)
IntroductionWith the development of global industrialization, metal minerals have become a global focal point of great power competition. An in-depth investigation into the evolution of global mineral trade structures, alongside an analysis of the relationships between metal minerals trade, resource endowments, industrialization, regional dynamics, and geopolitical competition, is crucial for nations to formulate effective trade policies and enhance the stability of global mineral trade development.MethodsThis study explores the evolution trends of the global metal minerals trade structure from 1990 to 2022 based on complex network and further detect community structure using the Infomap algorithm.Results and discussionThe results show that (1) There is a general upward trend in global metal minerals trade from 1990 to 2022, which can be segmented into phases of slow, rapid, and moderate growth. (2) The two major trading circles formed in the early stage with Japan and Europe as the center have changed, forming a dual pattern with China as the super demand center and Australia as the super supply center. (3) China, Australia, the U.S., Japan, Brazil, and the European Union play key roles in shaping the global trade network, with the structure of the global metal minerals trade network primarily being driven by demand centers. (4) According to the economic trends and the evolving resource demands, the global trade structure will translate from a concentrated bipolar model to a diversified network with multiple trade centers. The conclusion of this research helps specify international policies and maintain supply chain resilience.